1997
DOI: 10.1093/oxfordjournals.molbev.a025771
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite genetic distances between oceanic populations of the humpback whale (Megaptera novaeangliae)

Abstract: Mitochondrial DNA haplotypes of humpback whales show strong segregation between oceanic populations and between feeding grounds within oceans, but this highly structured pattern does not exclude the possibility of extensive nuclear gene flow. Here we present allele frequency data for four microsatellite loci typed across samples from four major oceanic regions: the North Atlantic (two mitochondrially distinct populations), the North Pacific, and two widely separated Antarctic regions, East Australia and the An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…The differentiation between samples can be estimated from microsatellite data using statistics based on alternative evolutionary models (ie an infinite allele model, Kimura and Crow, 1964; a stepwise mutation model, Kimura and Ohta, 1978). The most suitable statistical analyses to evaluate the genetic relationships between populations are still a matter of debate (Goodman, 1997;Valsecchi et al, 1997;Gaggiotti et al, 1999;Hardy et al, 2003). For comparative purposes, we chose to use three different methods.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation between samples can be estimated from microsatellite data using statistics based on alternative evolutionary models (ie an infinite allele model, Kimura and Crow, 1964; a stepwise mutation model, Kimura and Ohta, 1978). The most suitable statistical analyses to evaluate the genetic relationships between populations are still a matter of debate (Goodman, 1997;Valsecchi et al, 1997;Gaggiotti et al, 1999;Hardy et al, 2003). For comparative purposes, we chose to use three different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Winter sightings are reported from the Cape Verde Islands for example (Hazevoet & Wenzel, 2000). If whales using these other regions constitute a separate breeding group, and if these individuals primarily feed in the eastern regions of the North Atlantic as genetic results suggest (Valsecchi et al, 1997), then fewer animals from these eastern areas would travel to the West Indies. Alternatively, it has been suggested that not all humpback whales migrate or complete migration each year (Brown et al, 1995;Craig & Herman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Humpback whales are known to occur in the Cape Verde Islands in winter (Hazevoet & Wenzel, 2000), consistent with an eastern breeding area, though no re-sightings from this area have been confirmed. Genetic analysis of nuclear markers revealed a low but significant degree of heterogeneity between samples collected off Iceland and those collected in the western North Atlantic (Valsecchi et al, 1997). Recent findings that animals from Norwegian waters are sighted later in the West Indies season than the mean for other areas suggests that feeding ground origin may influence timing of occurrence in the West Indies.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As it is still a matter of debate which is the most suitable statistic model to describe genetic variation among samples (see Goodman, 1997;Valsecchi et al, 1997;Gaggiotti et al, 1999;Hardy et al, 2003), both models were used to analyse the data of this study: The IAM-based F ST (Wright, 1969), which can also be estimated by θ (Cockerham and Weir, 1984), and the SMMbased R ST (Slatkin, 1995) were calculated pairwise for all four populations using the Arlequin software v.2.000. F ST and R ST values were tested for significant departure from zero using permutation procedures implemented in Arlequin v.2.000.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%